Hematopoietic stem cell transplantation for children with primary immunodeficiency diseases: Single center experience in Jordan. (20th May 2013) - Amayiri, Nisreen; Al‐Zaben, Abdulhadi; Ghatasheh, Lubna; Frangoul, Haydar; Hussein, Ayad Ahmed
Abstract HSCT can be curative for many PID. Little is known about the outcome of HSCT for patients with PID in the developing countries. We retrospectively reviewed all children with PID who received HSCT at KHCC in Jordan between August 2003 and October 2011. Twenty‐eight patients were identified. The median age was 16 months (3 months–17 yr). Patients' diagnoses were SCID (n = 16), CHS (n = 3), HLH (n = 3), WAS (n = 2), Griscelli syndrome (n = 1), ALPS (n = 1), Omenn's syndrome (n = 1), and DiGeorge syndrome (n = 1). Seventeen patients received HLA‐matched related HSCT, eight received maternal un‐manipulated haploidentical HSCT, and three received unrelated cord blood transplantation. Nine patients (32%) developed BCGosis secondary to reactivation of pretransplant vaccination. Three died while still receiving anti‐tuberculosis drugs, one still on treatment, and all others have recovered. Six patients had graft failure; four of them received no conditioning regimens. At a median follow up of 32 months (range 1‐67), 21 patients are alive, with overall survival of 72%. We conclude that HSCT for PID patients can be performed with a good outcome in developing countries; however, delayed diagnosis or referral and BCG reactivation are unique challenges.